ANALISIS PENGELOLAAN ARSIP DI SEKRETARIAT DPRD KABUPATEN - Randi Saputra (Universitas Negeri Padang, 2018)
This study aims to reveal how the Analysis of Archive Management in the Secretariat of the Regency of Agam regency. The type of this research is descriptive and qualitative research, sampling technique used is Snowball Sampling technique with the number of informants 7 people. Data collection techniques used are observation, interviews and documentation with research instruments using interview guidelines. Data analysis techniques used are Miles and Huberman models. To test the validity of data used triangulation technique.The results of this study indicate that the archive management procedures in the secretariat of the Regency of Agam regency has not been implemented properly. It can be seen from 4 (four) cycles, namely: 1) Management of filing system, 2) Management of equipment and infrastructure, 3) problem management, 4) Management of Human Resource Management, from the four management there are problems in each - management. Those problems are. Management of filing systems where in archival system procedures use the time system, sometimes in the invention of the letter takes a long time in his invention. Management of equipment where facilities and infrastructure are inadequate or incomplete. Problem management is the number of damaged archives and even the archive is not found and the management of Human Resource Management is less in charge of qualification in the field of archives.Based on the above research the authors provide some suggestions in revamping the archive management procedures in the Secretariat of the Regency of Agam regency is the need for improvements made on the management of the archive. In addition, there should also be socialization or training for employees in the field of archives, and complete the facilities and infrastructure in the Secretariat of the Regency of AgamKeywords: Analysis, Archive